2023
DOI: 10.1021/acssuschemeng.3c01113
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Insulating Cellulose Nanofiber Aerogels from Brewery Residues

Abstract: Brewery spent grain (BSG), the main waste of the brewery industry, is often disposed of or sold as an animal feed at low prices, neglecting the potential for further valorization. In this work, BSG was used for the first time to produce cellulose nanofiber aerogels for green thermal insulating applications. Cellulose nanofibers (CNFs) were extracted from BSG through microfluidization with and without TEMPO-oxidation pretreatment to obtain bio-based building blocks for aerogels. The TEMPO-treated CNFs exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…According to several studies, CNF aerogels are found to have low density and high porosity, which makes them thermally insulating. 27,28 On the other hand, CNF aerogels are associated with some drawbacks, such as flammability, high moisture sensitivity, and low mechanical properties. To overcome these problems, MTMS, PU, and APP were used for the synthesis of a PU-based CNF aerogel.…”
Section: Resultsmentioning
confidence: 99%
“…According to several studies, CNF aerogels are found to have low density and high porosity, which makes them thermally insulating. 27,28 On the other hand, CNF aerogels are associated with some drawbacks, such as flammability, high moisture sensitivity, and low mechanical properties. To overcome these problems, MTMS, PU, and APP were used for the synthesis of a PU-based CNF aerogel.…”
Section: Resultsmentioning
confidence: 99%
“…Aerogels made from silane [1][2][3][4][5], carbon [6][7][8][9], biomass [10][11][12][13][14][15][16][17][18][19][20][21][22][23], polymers [24][25][26], metal oxides [27], inorganic salts [28,29], etc., have the advantages of low density, high porosity, and high specific area [18]. This combination of properties makes them have a huge number of applications in the fields of industry [30], architecture [8,31,32], agriculture [17], etc., some of which have been commercialized already. Among them, aerogels made from a soluble polymer matrix by freeze-drying have the potential to be applied to thermal or sound insulation because of their low cost, easy preparation, and low heat conductivity [1,9,30].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when water droplets condense on or are absorbed by the porous structure, the skeleton of the aerogel will be destroyed by capillary force and collapse [24]. Therefore, hydrophobic modification is a necessary precondition for the practical application of aerogels [15,31].…”
Section: Introductionmentioning
confidence: 99%
“…However, pulping, the process by which wood is reduced to a fibrous mass, requires strong chemical process resulting in emissions of sulfur compounds, suspended solids, and wastewater 7,8 . There has been also increasing efforts to keep wood in its solid form rather than disintegrating it to its biopolymeric constituents 9 . Utilizing plant‐based byproducts generated from agricultural production and food processing, as a nonwood cellulose resource, has huge benefits considering their sufficient resources and the smaller amount of lignin that requires less use of chemicals and energy to produce cellulose‐based materials 10 …”
Section: Introductionmentioning
confidence: 99%